Fetal and Neonatal Modified Myocardial Performance Indices in Preeclamptic versus Normotensive Pregnancies: A Prospective Cohort Study - Promket A; Duangkum C; Wongswadiwat Y; Saksiriwuttho P; Chaiyarach S; Kongwattanakul K; Komwilaisak R; Lumbiganon P; Sirikan P (Dove Medical Press, 2021)
Anutsara Promket,1 Chatuporn Duangkum,1 Yuttapong Wongswadiwat,2 Piyamas Saksiriwuttho,1 Sukanya Chaiyarach,1 Kiattisak Kongwattanakul,1 Ratana Komwilaisak,1 Pisake Lumbiganon,1 Prapassara Sirikan3 1Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Department of Pediatrics, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 3Department of Epidemiology and Biostatistics, Faculty of Public Health, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Chatuporn DuangkumDepartment of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, 123 Mittraphap Road, Muang District, Khon Kaen, 40002, ThailandTel +66 653241590Email Chatudu@kku.ac.thObjective: To compare fetal and neonatal cardiac functions in terms of global, systolic, and diastolic function between the preeclampsia and normotensive blood pressure of pregnancies.Methods: A prospective cohort study was conducted at a university hospital in Northeast Thailand. Twenty-nine pregnancies diagnosed as preeclampsia with or without severe features were compared with 29 normotensive pregnancies. Global cardiac, systolic, and diastolic function were assessed at prenatal and postnatal periods, by a professionally trained obstetrician and pediatric cardiologist, respectively.Results: The fetal left modified myocardium performance index (Mod-MPI) in preeclampsia and normotensive blood pressure were 0.60± 0.08 and 0.59± 0.08 (p-value=0.341), respectively, while fetal right Mod-MPI were 0.57± 0.16 and 0.54± 0.21 (p-value=0.861), respectively. There were no statistically significant differences in terms of fetal isovolumic contraction time (ICT), isovolumic relaxation time (IRT), ejection time (ET), aortic peak systolic velocity (Ao PSV), pulmonary artery peak systolic velocity (PA PSV), mitral valve (MV) E:A ratio, or tricuspid valve (TV) E:A ratios between the two groups. Neonatal mitral valve E peak systolic velocity (MV-E PV) in preeclamptic and normotensive blood pressure groups were significantly different at 51.1± 8.02 cm/s and 43.56± 5.21cm/s (p-value=0.036), respectively, whereas neonatal left Mod-MPI, mitral valve A peak systolic velocity (MV-A PV), MV E:A ratio, and Ao PSV were not significantly different (p-value=0.436, 0.119, 0.379, and 0.709), respectively.Conclusion: Neonatal MV-E PV of the preeclampsia group was significantly higher than the normotensive blood pressure group, while there were no statistically significant differences in terms of global cardiac and diastolic functions during the fetal period between two groups.Keywords: fetal Mod-MPI, neonatal Mod-MPI, preeclampsia, normotensive